Enhancing compassion in medical education - a comparative study of the efficacy of clinical clerkships versus simulation-based training methodologies - Claudia Ebm; R. Sarti; P. Panico; M. Pagliotta; V. Vinci; S. Oldani (BMC Medical Education)
Highlights Compassion at follow-up was significantly higher among the clerkship group in this longitudinal study. Immersion in realistic clinical settings may promote compassion among medical students.